Association between Parathyroid Hormone and Anemia: A Cross-Sectional Observational Study of maintenance Hemodialysis Patients of a Tertiary Care Center - Junejo, Abdul Mnannan; Ali, Muhammad; Ahmad, Shafique; Ejaz, Ayesha; Iram, Hina; Kumar, Sandeep (Pakistan Journal of Kidney Diseases, 2021)
Objective The objective of this study was to assess the relationship between intact parathyroid hormone levels (iPTH) and hemoglobin (Hb) levels in patients with end-stage renal disease (ESRD) who were on hemodialysis. Material and methods An observational, cross-sectional study was conducted in the Department of Nephrology at Jinnah Postgraduate Medical Centre in Karachi, Pakistan. Patients were enrolled in this study after consent and institutional review board approval. Serum samples were collected for Hb level, iPTH level, vitamin D, urea and creatinine, ferritin, and transferrin saturation. Results Ninety four patients were inducted into this study; men comprised 66.0% of the patients, and Diabetes mellitus was the commonest etiology of ESRD. Most of the patients were on dialysis for more than 5 years on twice per week hemodialysis. Mean Hemoglobin was 9.29g/dl, iPTH 576.59ng/dl and Vitamin D 25.47ng/ml. Significant inverse correlation was found between anemia and i-PTH levels. Conclusion Hyperparathyroidism is one of the major contributor anemia among maintenance hemodialysis patients.